Biogeography and evolution of the vertebrate fauna in campo rupestre , a megadiverse Neotropical montane open ecosystem - Oswald, Caroline B; Silveira, Fernando A O; Cornelissen, Tatiana; Costa, Lílian M; Costa, Henrique C; Dagosta, Fernando C P; Domingos, Fabricius M C B; Eterovick, Paula C; Freitas, Guilherme H S; Guedes, Thaís B; Guerra, Tadeu J; Goulart, Fernando F; et al. (Biological journal of the Linnean Society, 2025)
Mountains are hotspots of biodiversity and endemism, but biogeography and diversification in tropical montane grasslands remain poorly understood. We reviewed hypotheses explaining the origin of vertebrate fauna ranging from phylogeography to community-scale patterns, while also considering historical biogeography and macroevolutionary dynamics in campo rupestre in the Espinhaço Range. We conducted a systematic review of papers published in 1945–2023 on vertebrate ecology, biogeography, and diversification in campo rupestre. The vertebrate fauna of campo rupestre is characterized by high levels of biodiversity and endemism relative to area extent across most taxa. Unfortunately, such diversity is increasingly threatened, with ~20% of endemic species listed on the IUCN Red List. Hummingbirds are key pollinators, whereas seed dispersal is performed primarily by generalist birds, small mammals, and lizards. A combination of isolation, range shifts, and species persistence played key roles in shaping diversification dynamics in these ancient mountains. High levels of diversity, endemism, and the occurrence of threatened species underscore the pressing need for funding conservation of the outstanding biodiversity in the Espinhaço Range. We propose a research agenda to fill knowledge gaps and promote research needed to provide a more complete understanding of the biogeographical scenario and accelerate protection strategies.